Growth differentiation factor‐15 is associated with muscle mass in chronic obstructive pulmonary disease and promotes muscle wasting in vivo. Issue 4 (29th December 2015) - Patel, Mehul S.; Lee, Jen; Baz, Manuel; Wells, Claire E.; Bloch, Susannah; Lewis, Amy; Donaldson, Anna V.; Garfield, Benjamin E.; Hopkinson, Nicholas S.; Natanek, Amanda; Man, William D‐C; Wells, Dominic J.; et al.
Abstract: Background: Loss of muscle mass is a co‐morbidity common to a range of chronic diseases including chronic obstructive pulmonary disease (COPD). Several systemic features of COPD including increased inflammatory signalling, oxidative stress, and hypoxia are known to increase the expression of growth differentiation factor‐15 (GDF‐15), a protein associated with muscle wasting in other diseases. We therefore hypothesized that GDF‐15 may contribute to muscle wasting in COPD. Methods: We determined the expression of GDF‐15 in the serum and muscle of patients with COPD and analysed the association of GDF‐15 expression with muscle mass and exercise performance. To determine whether GDF‐15 had a direct effect on muscle, we also determined the effect of increased GDF‐15 expression on the tibialis anterior of mice by electroporation. Results: Growth differentiation factor‐15 was increased in the circulation and muscle of COPD patients compared with controls. Circulating GDF‐15 was inversely correlated with rectus femoris cross‐sectional area ( P  < 0.001) and exercise capacity ( P  < 0.001) in two separate cohorts of patients but was not associated with body mass index. GDF‐15 levels were associated with 8‐oxo‐dG in the circulation of patients consistent with a role for oxidative stress in the production of this protein. Local over‐expression of GDF‐15 in mice caused wasting of the tibialis anterior muscle that expressed it but not in the contralateral muscle suggesting a direct effect of GDF‐15 on muscle mass ( P  < 0.001). Conclusions: Together, the data suggest that GDF‐15 contributes to the loss of muscle mass in COPD.